Diversity of endophytic bacterial microbiota in grapevine shoot xylems varies depending on wine grape-growing region, cultivar, and shoot growth stage - Hamaoka, Kazuhiro; Aoki, Yoshinao; Takahashi, Sayuri; Enoki, Shinichi; Yamamoto, Kosuke; Tanaka, Keisuke; Suzuki, Shunji (Scientific reports, 2022)
Next-generation sequencing technology may clarify microbiota that are as yet poorly understood in the soil, the rhizosphere, and the phyllosphere of vineyards. To provide new information on the interaction between grapevine and microorganisms, we focused on the endophytic microbiota in grapevine. We performed endophytic microbiome analysis of the shoot xylems of four cultivars, Vitis vinifera cvs. Chardonnay, Pinot Noir, Cabernet Sauvignon, and Vitis sp. cv. Koshu, grown in eleven vineyards in Japan. The number of endophytic fungal species was small in the grapevine shoot xylems and could not be analyzed further, whereas a total of 7,019,600 amplicon sequences (46,642–285,003 per shoot xylem) and 1305 bacterial operational taxonomic units were obtained by analysis of the V3–V4 region of the bacterial 16S rRNA gene. Gammaproteobacteria was predominant in the shoot xylems at the shoot elongation stage irrespective of the cultivar, whereas Alphaproteobacteria and Oxyphotobacteria were predominant at véraison. Actinobacteria, Bacteroidia, Bacilli, and Clostridia were also detected in the shoot xylems. The endophytic bacterial microbiota in Koshu and Pinot Noir shoot xylems were similar irrespective of the grapevine-growing region. In contrast, the endophytic bacterial microbiota in Chardonnay and Cabernet Sauvignon showed diversity and complexity among grapevine-growing regions. Alpha diversity analysis revealed that Koshu shoot xylems had a higher diversity of endophytic bacterial microbiota than Pinot Noir, Chardonnay, and Cabernet Sauvignon shoot xylems, and that grapevine shoot xylems at the shoot elongation stage had a higher diversity of endophytic bacterial microbiota than those at véraison. Principal coordinate analysis (PCoA) demonstrated that the profiles of the endophytic bacterial microbiota in grapevine shoot xylems at véraison were relatively uniform compared with those at the shoot elongation stage. Multidimensional scaling analysis showed that the plots of all cultivars were generally apart from each other at the shoot elongation stage and then became close to each other at véraison. The plots of all grapevine-growing regions cultivating Koshu were close to each other, whereas those of grapevine-growing regions cultivating Chardonnay and Cabernet Sauvignon were apart from each other. The findings of this study suggest that the endophytic bacterial microbiota in grapevine shoot xylems varied depending on the cultivar and the grapevine-growing region even for the same cultivars, and that the microbiota fluctuated depending on the shoot growth stage.